Boosting trade finance in developing countries: What link with the WTO? - Marc Auboin (World Trade Organization (WTO), 2007)
The paper discusses the efforts deployed by various players, mainly multilateral financial institutions, regional development banks, export credit agencies, to mobilize greater flows of trade finance for developing countries, with a view to help them integrate in world trade. As an institution geared towards the balanced expansion of world trade, the WTO is in the business of making trade possible. Its various functions include reducing trade barriers, negotiating and implementing global trade rules, and settling disputes on the basis of the rule of law. The WTO is also interested in strengthening the supply-side of developing countries so that they can respond to new market opportunities. To this end, it supports various initiatives aimed at improving the trade infrastructures of developing countries, ranging from the ability to meet international product, safety and sanitary standards, to run efficient customs, or to participate effectively to the multilateral trade negotiations by training public servants. The WTO carries out various initiatives with other partners (public and private sector institutions), in the context of its own technical assistance program, or in the context of multi-agency projects such as the Integrated Framework or the Aid-for-Trade Initiative. Since more than 90% of trade transactions involve some form of credit, insurance or guarantee, one can reasonably say that trade finance is the lifeline of trade. Producers and traders in developing or least-developed countries need to have access to affordable flows of trade financing and insurance to be able to import and export, and hence integrate in world trade. From that perspective, an efficient financial system is one indispensable infrastructure to allow trade to happen. In line with the above initiatives, the WTO has been following actively, and at times, directly supporting, initiatives to boost the availability of trade finance in developing and least-developed countries wherever it was needed. Since the WTO is not a financial institution, it has been supporting in the past few years partners engaged in this effort such as international financial institutions, export credit agencies, large banks and regional development banks. (...) This paper provides background on the difficulties of some countries and traders to access affordable trade credit and finance, on the growing divide between these low income countries and economically advanced countries in handling modern trade finance instruments, and on the joint reflection undertaken by the WTO, most recently under the Aid-for-Trade programme, and previously under the umbrella of the WGTDF and the Coherence Mandate, to help strengthen developing countries' capacities in this area.
Keywords: E44; F13; F34; F36; O19; 330; Trade financing; cooperation with international financial institutions; aid-for-trade; coherence; Außenhandelsfinanzierung; Entwicklungsländer